2016
DOI: 10.1007/s13340-016-0275-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of switching from insulin glargine to insulin degludec in patients with type 1 diabetes: a 16-week retrospective study

Abstract: We retrospectively investigated the effect of switching from insulin glargine (IGlar) to insulin degludec (IDeg) on glycemic control in Japanese patients with type 1 diabetes mellitus. We also evaluated the dose of IDeg, and assessed weight gain and the risk of hypoglycemia after switching. Forty-five patients with type 1 diabetes were switched from IGlar (once daily or twice daily) to IDeg (once daily) during routine medical care. Data were collected for 16 weeks after switching from IGlar to IDeg. The mean H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Therefore, approximately half (40%-60%) of total daily insulin doses in patients with T1D using multiple daily injections is given as basal insulin, dependent on body weight and insulin sensitivity, and the rest is divided into meal-related doses, mainly based on carbohydrate content 38 39. In our population, daily basal insulin doses were 58% of the daily total doses, similarly to other national studies in T1D reporting that daily basal doses ranged 55%-63% of daily total insulin doses and could be explained, in part, for Mediterranean diet and lifestyle followed by the Spanish populations,20 40 in contrast with studies in other countries in patients with T1D where daily basal insulin requirements usually are ≤50% 21 27 31 39…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Therefore, approximately half (40%-60%) of total daily insulin doses in patients with T1D using multiple daily injections is given as basal insulin, dependent on body weight and insulin sensitivity, and the rest is divided into meal-related doses, mainly based on carbohydrate content 38 39. In our population, daily basal insulin doses were 58% of the daily total doses, similarly to other national studies in T1D reporting that daily basal doses ranged 55%-63% of daily total insulin doses and could be explained, in part, for Mediterranean diet and lifestyle followed by the Spanish populations,20 40 in contrast with studies in other countries in patients with T1D where daily basal insulin requirements usually are ≤50% 21 27 31 39…”
Section: Discussionsupporting
confidence: 71%
“…In RWS with patients with T1D, switching to IDeg from IGla-100 or detemir is associated with a 12%-13% reduction of both basal and prandial daily insulin doses,18 21 28 mainly in patients who were previously on two injections of basal insulin. However, other studies in real-life conditions informed that IDeg doses in patients with T1D transferred from IGla-100 once-daily were equivalent 2527 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the same study reported that insulin glargine (U300) users had higher insulin dose requirements when compared to insulin degludec (U100) users [ 20 ]. A Japanese study revealed that switching to insulin degludec resulted in better glycemic control in 16 weeks with lower insulin dosing requirements [ 21 ]. Similarly, real-world data reported a significant reduction in HbA1c, which was achieved after switching to insulin degludec, irrespective of the type of diabetes and the type of prior long-acting insulin, and with lower insulin requirements [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the importance of complementing clinical trial results with real-world evidence has been widely recognized, with the aim of assessing the generalizability of results from RCTs to wider, less selected populations [11,12]. Several real-world studies have evaluated the effectiveness and safety of insulin degludec [13][14][15][16][17][18][19][20][21][22][23][24] in routine clinical practice. However, none of these studies have prospectively collected information on hypoglycemic events.…”
Section: Introductionmentioning
confidence: 99%